Combined modelling and miniaturised characterisation of high-temperature forging in a nickel-based superalloy. (15th December 2018) - Alabort, E.; Reed, R.C.; Barba, D.
Abstract: Continuum models and miniaturised experiments are used to elucidate the high-temperature forgeability of the Ni-based superalloy Inconel 903. Uniaxial compression high temperature tests allow the derivation of an apparent activation energy and the strain rate sensitivity of the deformation process, and to propose a unified constitutive model that captures the underlying physics of deformation. Metallographic analysis is then used to elucidate changes in microstructure which arise during the deformation process; microstructure evolution models which define the changes in grain size and recrystallisation during high temperature compression are proposed. Miniaturised forging experiments in double-cone specimens validate the modelling approach under relevant forging conditions at different temperatures and deformation rates. Finally, the deformation behaviour of this material in an industrially relevant manufacturing scenario – the forging process of a turbine disc – is studied numerically. Graphical Abstract: Highlights: Uniaxial compression tests between 900–1100°C are used to elucidate the forging performance of the nickel superalloy IN903. A visco-plastic model with explicit microstructure dynamics is proposed and calibrated to our experimental observations. Forging simulators of double-cone experiments validate temperature, strain-rate and microstructure dependence of the model. The application of the framework is highlighted with an industry-relevant process model: the forging of a turbine disc.